Pengaruh Diklat, Kepemimpinan dan Penerapan Budaya Organisasi Terhadap Kinerja Karyawan - Ardianta, I Wayan; Supartha, I Wayan Gede (E-Jurnal Manajemen, 2014)
Polemic today's business world requires the optimization of the utilization and quality of human resources of the company. The success of an organization is strongly influenced by the performance of individual karyawannya.Penelitian aims to analyze the effect of training (education and training), leadership, and organizational culture, either simultaneously or partially on employee performance in Hotel Legian-Kuta Bali Dwipa. The results indicate that training, leadership, organizational culture and the implementation of partial and simultaneous positive and significant impact on employee performance Dwipa Hotel Bali.
Keywords: training, leadership, organizational culture, performance